Correlation of head size and height with dental age - Brilliant Hardika Putra Prasetyawan; Astika Swastirani; Nabilah Shafiyyah Rahmayati; Sari Kurniawati (Faculty of Dental Medicine Universitas Airlangga, 2026)
Background: Age estimation plays an important role in both dentistry and forensics. Today, the London Atlas method is widely used by the students or researchers, but biological growth (head dimensions and body height) may also provide a guide about the developmental stage of humans. Purpose: To evaluate the correlation between head size with body height to match with dental age to determine the biological dan chronological age. Methods: Using cross sectional study to 51 samples with age from 4 until 20 years. Head length, head width, body height, and dental panoramic photo were recorded for each sample. Statistical analysis using Spearman correlation tests and linear regression to compare with many variables. Results: Positive correlation between body height and dental age (r = 0.892; p < 0.001). Head length (r = 0.475; p < 0.001) and head width (r = 0.477; p < 0.001) show moderate correlations with dental age. Next, the ratio of head length to body height shows a significant correlation with chronological age (p < 0.001; R² = 0.614), but the cephalic index shows no significant correlation with either dental age or chronological age. Conclusion: Head length and body height are significantly correlated with dental age (London Atlas method), so that it can be useful for age estimation. .